2014
DOI: 10.1002/adma.201400373
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Water Drop Energy by a Sequential Contact‐Electrification and Electrostatic‐Induction Process

Abstract: A new prototype triboelectric nanogenerator with superhydrophobic and self-cleaning features is invented to harvest water drop energy based on a sequential contact electrification and electrostatic induction process. Because of the easy-fabrication, cost-effectiveness, and robust properties, the developed triboelectric nanogenerator expands the potential applications to harvesting energy from household wastewater and raindrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
515
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 682 publications
(526 citation statements)
references
References 35 publications
8
515
2
1
Order By: Relevance
“…39 Technologically, such measurements could be valuable as Teflon substrates that exhibit micro-nanoscale surface roughness are being explored for energy harvesting with impinging water droplets. 40 In addition, the carbon working electrodes were functionalized with hydrous iridium oxide (IrOx) to create a pH responsive electrode 31 to follow the local pH change during the initial dissolution of a pristine calcite crystal surface. For this measurement, a functionalized quadprobe was filled with 10 mM KCl solution (pH 6.8) and brought into contact with a freshly cleaved calcite surface to form a thin layer electrochemical cell between the probe and crystal surface ( Figure 4C).…”
Section: +mentioning
confidence: 99%
“…39 Technologically, such measurements could be valuable as Teflon substrates that exhibit micro-nanoscale surface roughness are being explored for energy harvesting with impinging water droplets. 40 In addition, the carbon working electrodes were functionalized with hydrous iridium oxide (IrOx) to create a pH responsive electrode 31 to follow the local pH change during the initial dissolution of a pristine calcite crystal surface. For this measurement, a functionalized quadprobe was filled with 10 mM KCl solution (pH 6.8) and brought into contact with a freshly cleaved calcite surface to form a thin layer electrochemical cell between the probe and crystal surface ( Figure 4C).…”
Section: +mentioning
confidence: 99%
“…Structures are always obtained by the employment of a thin film of piezoelectric substrate encapsulated in an insulator shield. The first one is the cantilever structure, used in [9][10][11][12][13][14][15], in which the piezoelectric structure has one end bound while the other is free to move. Such structures allow a low damped movement as a result of the collision with the raindrops.…”
Section: Harvestersmentioning
confidence: 99%
“…A recent work of Helseth [14] introduces different possibilities to harvest raindrop energy with piezoelectric and triboelectric transducers and evaluates the energy potential due to rain parameters. Lin et al [15] with a pioneering work suggested a recover energy of 30 nJ of electrical energy due to a droplet of 30 mL. These results leave some uncertainty on the actual capability to generate an adequate amount of electrical energy from rain.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the low-cost, chemical stable, lightweight, small-sized, and high efficient triboelectric nanogenerators (TENGs), which can directly convert the mechanical energy in the environment to electric energy, can minimize the problem. [8][9][10][11][12] Herein we report a nanowire based TENG to collect the blue energy from ocean and its great potential for applications. First, the nanowire, which will largely add the roughness of surface and thus magnificently increase the contacting area of the FEP film and water, is fabricated by etching.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%